Nilai Religiositas pada Film animasi Si Bulan Koki Super sebagai Materi Pendidikan Islami - Musdalifah; dudi suhardini, asep (Bandung Conference Series: Islamic Education, 2024)
Abstract. The value of religiosity must be instilled from as early as possible, this helps shape children's religious character. A number of recent viral incidents have shown the fact that children's morals are declining due to a lack of religious education, many children go to school but cannot understand the lessons well. In the increasingly advanced digital era, learning to use digital media can be utilized, such as by showing Islamic animated films. This can help children who can only learn from watching examples more easily understand the lessons from the films shown. The animated film Si Bulan Koki Super is an Islamic film which instills religious values ​​which are easy to understand because the values ​​are explained in a show that has nuances of everyday life. This can be used as educational material because the religious values ​​contained in this film contain the basic points needed in Islamic educational material. This research aims to determine the religious value contained in the animated film Si Bulan Koki Super and also that this value can be used as Islamic education material. This research uses a qualitative descriptive approach, collecting data by observation and documentation. Data analysis uses pierce theory semiotic analysis, namely using the meaning triangle theory; Research shows that in the animated film The Super Chef Moon, there is a religious value that can be used as Islamic education material. Abstrak. Penanaman nilai religiositas harus dari sedini mungkin, hal ini membantu pembentukan karakter religious anak. Sejumlah kejadian viral belakangan ini dengan fakta merosotnya moral anak karena kurangnya Pendidikan agama, banyak anak yang bersekolah namun tidak dapat mencerta pelajaran dengan baik. Di era digital yang semakin maju, dapat dimanfaatkan dengan pembelajaran menggunakan media digital seperti dengan menayangkan film animasi islami. Hal ini dapat membantu anak yang hanya bisa belajar dari melihat contoh lebih mudah memahami pelajaran dari film yang ditayangkan. Film animasi Si Bulan Koki Super adalah film islami yang didalamnya menanamkan nilai religiositas yang mudah dipahami karena nilai dijelaskan dalam tayangan yang bernuansa kehidupan sehari-hari. Hal ini dapat dijadikan sebagai materi Pendidikan karena nilai religiositas yang terkandung dalam film ini mengandung pokok dasar yang diperlukann dalam materi Pendidikan islami. Penelitian ini bertujuan untuk mengetahui nilai religiositas yang terkandung dalam film animasi Si Bulan Koki Super dan juga nilai tersebut dapat dijadika materi Pendidikan islami. Penelitian ini menggunakan pendekatan deskriftif kualitatif, pengumpulan data dengan observasi dan dokumentasi. Analisis data menggunakan analisis semiotic teori pierce yaitu menggunakan teori segitiga makna.hasi; penelittian menunjukan bahwa dalam film animasi si bulan koki super terdapat nilai religiositas yang dapat dijadikan materi Pendidikan islami